The City and the Critique of Labour in Interwar Cinema: The Surrealist Background of René Clair’s Early Films - Dominguez Muñoz, Jésica; Sousa Pardo, Carmen; Valle Corpas, Irene (Re-visiones, 2026)
This article examines René Clair's contribution to interwar cinema and early Surrealism through a study of his film productions from the 1920s and 1930s. For this purpose, we examine some of his emblematic films as well as other lesser-known works, through various essential categories of Surrealism, drawing on both Walter Benjamin's interpretation of the movement and testimonies from some of its members. We delve deeper into the image of the modern city as portrayed by the avant-garde, seeking similarities and points of divergence between Clair’s films and other European cinematographic and photographic contemporary movements. Ultimately, the aim is to determine the politics of time, space, desire and work defined by Clair, and to explore the key strategies he employed when filming the urban phenomenon.
Keywords: René Clair; surrealism; cinema and city; cinematographic time; historical avant-garde; Walter Benjamin; desire